Abnormal γ″ - ε phase transformation in the CoCrFeNiNb0.25 high entropy alloy. (15th March 2018) - He, Feng; Wang, Zhijun; Wang, Jing; Wu, Qingfeng; Chen, Da; Han, Bin; Li, Junjie; Wang, Jincheng; Kai, J.J.
Abstract: Thermodynamically, the multi-principal-component compositions of high entropy alloys (HEAs) bring diversified phase transformation paths. In this study, we report that a γ″ phase precipitates from the face centered cubic (FCC) matrix and then abnormally transforms into a ε phase, instead of the δ phase as reported in superalloys. The ε phase has a (NiCo)3 Nb-type hexagonal crystal structure. The phase transformation takes places in a manner of peritectoid reaction: γ″ + FCC → ε. The present findings indicate a high probability for researchers to find new efficient strengthening phases as well as interesting phase transformation mechanism in HEAs. Graphical abstract: Image 1